Efficient Non-fullerene Organic Solar Cells Enabled by Sequential Fluorination of Small-Molecule Electron Acceptors - Xie, Ruihao; Ying, Lei; Liao, Hailong; Chen, Zhongxin; Huang, Fei; Cao, Yong (Frontiers in Chemistry, 2018)
Three small-molecule non-fullerene electron acceptors containing different numbers of fluorine atoms in their end groups were designed and synthesized. All three acceptors were found to exhibit relatively narrow band gaps with absorption profiles extending into the near-infrared region. The fluorinated analogues exhibited enhanced light-harvesting capabilities, which led to improved short-circuit current densities. Moreover, fluorination improved the blend film morphology and led to desirable phase separation that facilitated exciton dissociation and charge transport. As a result of these advantages, organic solar cells based on the non-fullerene acceptors exhibited clearly improved short-circuit current densities and power conversion efficiencies compared with the device based on the non-fluorinated acceptor. These results suggest that fluorination can be an effective approach for the molecular design of non-fullerene acceptors with near-infrared absorption for organic solar cells.